2019
DOI: 10.1530/joe-18-0287
|View full text |Cite
|
Sign up to set email alerts
|

AAV8-mediated gene transfer of microRNA-132 improves beta cell function in mice fed a high-fat diet

Abstract: MicroRNAs have emerged as essential regulators of beta cell function and beta cell proliferation. One of these microRNAs, miR-132, is highly induced in several obesity models and increased expression of miR-132 in vitro modulates glucose-stimulated insulin secretion. The aim of this study was to investigate the therapeutic benefits of miR-132 overexpression on beta cell function in vivo. To overexpress miR-132 specifically in beta cells, we employed adeno-associated virus (AAV8)-mediated gene transfer using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 30 publications
0
19
0
3
Order By: Relevance
“…No link between miR-132 expression and pancreatitis was reported so far. However, miR-132 expression is reported to be upregulated in beta cells of the pancreas in response to hyperglycemia and obesity 56,57 . In previous studies we could prove that hyperglycemia is not observed during a cerulein induced pancreatitis 58,59 .…”
Section: Discussionmentioning
confidence: 99%
“…No link between miR-132 expression and pancreatitis was reported so far. However, miR-132 expression is reported to be upregulated in beta cells of the pancreas in response to hyperglycemia and obesity 56,57 . In previous studies we could prove that hyperglycemia is not observed during a cerulein induced pancreatitis 58,59 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently several candidates are in phase 1 and phase 2 clinical trials, e.g., a locked nucleic acid (LNA)-based drug to inhibit miR-92 has potential in wound healing (70). In attempts to treat T2D, studies in animal models have used strategies that could be potentially translated to humans (71)(72)(73). Different approaches to silence the miRNAs using chemically modified antagomirs have been employed in these studies.…”
Section: Mirnas As Therapeutic Tools In Diabetes Treatmentmentioning
confidence: 99%
“…Mulder et al used a different approach to treat high-fat diet fed mice. In this case, the authors generated an AAV8 construct that enables the overexpression of miR-132 [66], a miRNA with a beneficial impact on β-cell function and that is normally involved in the adaptation of β-cells to insulin resistance (see above). The expression of the construct was under the control of the rat insulin promoter and was therefore restricted to β-cells [66].…”
Section: Mirnas As Potential Therapeutic Targets For T2dmentioning
confidence: 99%
“…In this case, the authors generated an AAV8 construct that enables the overexpression of miR-132 [66], a miRNA with a beneficial impact on β-cell function and that is normally involved in the adaptation of β-cells to insulin resistance (see above). The expression of the construct was under the control of the rat insulin promoter and was therefore restricted to β-cells [66]. Interestingly, overexpression of miR-132 did not affect glucose homeostasis in mice kept on regular chow diet but enhanced insulin secretion and increased β-cell proliferation in mice on high-fat diet, resulting in improved blood glucose control [66].…”
Section: Mirnas As Potential Therapeutic Targets For T2dmentioning
confidence: 99%
See 1 more Smart Citation